Chatbots and Customer Satisfaction in E-Commerce: An Exploratory Study - Kamelia, Kamelia; Nawawie, Gerald Haryadi; Satriana, Imelda; Sucipto, Anthony Joshua (Journal of Business, Management, and Social Studies, 2024)
This study tries to analyze how the implementation of chatbots, with their capabilities for fast responsiveness and personalized service, influences customer satisfaction in the e-commerce context. Given the nature of the research question, the study could potentially employ a quantitative methodology to measure and analyze the relationship between chatbot features (like responsiveness and personalization) and customer satisfaction levels. This might involve surveys – Collecting data from e-commerce customers about their experiences with chatbots and their overall satisfaction. The study’s findings indicate a significant positive correlation between chatbot usage and key e-commerce outcomes, revealing that chatbots enhance customer satisfaction through fast, responsive, user-friendly, and personalized services, which in turn drives increased site revisits, repurchase intentions, and positive word-of-mouth. Therefore, the effective implementation of chatbots is crucial for boosting customer satisfaction and fostering positive consumer behavior in the e-commerce sector. Based on the provided findings and the suggestion for future research, the novelty of this study appears to lie in empirically demonstrating the multifaceted positive impact of chatbot implementation on crucial e-commerce metrics – specifically customer satisfaction, repurchase intentions, site revisits, and word-of-mouth – by highlighting the mediating role of enhanced service qualities like speed, responsiveness, ease of use, and personalization.